Powtoon Media for the Understanding of Deaf Mathematics - Siti Mandalawati, Iis; Jihad, Asep; Sugilar, Hamdan (KnE Social Sciences, 2024)
This study aims to determine the role of Powtoon animation media on the understanding of deaf students in mathematical arithmetic operations. This study uses mixed methods so that the data is generated from the observation process described in percentages. The subjects of this study were 3 deaf students of class VIII SMP-LB. The research data collection used observation sheet instruments, test questions instruments, and open questionnaires. The results showed that the animated Powtoon media played a very good role in the interests, attitudes, motivation, and involvement of students in the learning process that increased students’ understanding abilities. The research is expected to contribute in creating an innovative learning process with the help of visual media for deaf students. It is hoped that there will be more attractive visual media, so that the deaf students can achieve their learning goals in the process of learning mathematics. Keywords: deaf, powtoon media, understanding mathematics.